The impact of loneliness on depression, mental health, and physical well-being - Oluwasegun Akinyemi; Waliah Abdulrazaq; Mojisola Fasokun; Fadeke Ogunyankin; Seun Ikugbayigbe; Uzoamaka Nwosu; Miriam Michael; Kakra Hughes; Temitope Ogundare (PLoS ONE, 2025)
Background Loneliness is a growing public health concern, with substantial implications for mental and physical health. Despite increasing attention, it remains an underrecognized determinant of health outcomes in population-based research. Objective This study evaluates the association between loneliness and key health outcomes, including depression diagnosis, poor mental health days, and poor physical health days, using a nationally representative sample. Methods We analyzed Behavioral Risk Factor Surveillance System (BRFSS) data from 2016 to 2023. Loneliness was measured with the question, “How often do you feel lonely?” and categorized into five levels: Always, Usually, Sometimes, Rarely, and Never. We estimated average treatment effects (ATE) using inverse probability weighting (IPW), adjusting for sociodemographic characteristics and incorporating BRFSS sampling weights and fixed effects for state, and year. Results The study included 47,318 individuals, predominantly White (73.3%), female (62.1%), and aged 18–64 years (72.1%). Over 80% of participants reported some degree of loneliness. Compared to those who reported “Never” being lonely, individuals who reported being “Always” lonely had a significantly higher predicted probability of depression (50.2% vs. 9.7%, ATE = +40.5 percentage points, p < 0.001), 10.9 more poor mental health days, and 5.0 more poor physical health days per month (all p < 0.001). Disparities were evident across sex, race/ethnicity, and age. Women consistently reported more poor mental health days than men across most loneliness levels. Black individuals reporting loneliness had significantly lower probabilities of depression and fewer poor mental health days than White peers. Older adults (>64) experienced more poor physical health days than younger adults across all loneliness categories. Conclusion Loneliness is a strong and independent predictor of depression and poor health outcomes. Public health interventions aimed at addressing loneliness—especially among high-risk subgroups—are critical to improving mental and physical well-being at the population level.